Interferon-alpha responsible EPN3 regulates hepatitis B virus replication - Li, Xueqian; Wang, Zhe; Zhou, Weiping; Fu, Xuanhe; Zhang, Yunpeng; Sun, Ye; Yang, Biao; Bai, Yuxin; Dai, Chunwei; Xu, Xiaolun; Cui, Fan; Zhao, Ying; et al. (Frontiers in Medicine, 2022)
Hepatitis B virus (HBV) infection remains a major health problem worldwide, and the current antiviral therapy, including nucleoside analogues, cannot achieve life-long cure, and clarification of antiviral host immunity is necessary for eradication. Here, we found that a clathrin-binding membrane protein epsin3 (EPN3) negatively regulates HBV-RNA. EPN3 expression was induced by transfection of an HBV replicon plasmid, and reduced HBV-RNA level in hepatic cell lines and murine livers hydrodynamically injected with the HBV-replicon plasmid. Viral RNA reduction by EPN3 was dependent on transcription, and independent from epsilon structure of viral RNA. Viral RNA reduction by overexpression of p53 or IFN-α treatment, was attenuated by knockdown of EPN3, suggesting its role downstream of IFN-α and p53. Taken together, this study is the first to demonstrate the anti-HBV role of EPN3. The mechanism how it decreases HBV transcription is discussed.